1997
DOI: 10.1007/s002030050527
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 16S rRNA and methane monooxygenase gene sequences reveals a novel group of thermotolerant and thermophilic methanotrophs, Methylocaldum gen. nov.

Abstract: Two methanotrophic bacteria with optimum growth temperatures above 40 degrees C were isolated. Thermotolerant strain LK6 was isolated from agricultural soil, and the moderately thermophilic strain OR2 was isolated from the effluent of an underground hot spring. When compared to the described thermophilic methanotrophs Methylococcus capsulatus and Methylococcus thermophilus, these strains are phenotypically similar to Methylococcus thermophilus. However, their 16S rRNA gene sequences are markedly different from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
124
1
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 190 publications
(128 citation statements)
references
References 0 publications
2
124
1
1
Order By: Relevance
“…One additional type of gammaproteobacterial methanotrophs, type X, was originally proposed for Methylococcus capsulatus, which, in addition to ribulose monophosphate pathway, possesses ribulose-1,5-bisphosphate carboxylase/oxygenase (RubisCO), a key enzyme in the Calvin-Benson cycle (Whittenbury and Dalton, 1981;Whittenbury, 1981). Several Methylococcus-related methanotrophs have been described including the genera Methylocaldum (Bodrossy et al, 1997;Takeuchi et al, 2014), Methyloparacoccus (Hoefman et al, 2014) and Methylogaea (Geymonat et al, 2010). Members of these genera form a monophyletic cluster in pmoA gene-based trees and are lately addressed as type Ib methanotrophs.…”
Section: Introductionmentioning
confidence: 99%
“…One additional type of gammaproteobacterial methanotrophs, type X, was originally proposed for Methylococcus capsulatus, which, in addition to ribulose monophosphate pathway, possesses ribulose-1,5-bisphosphate carboxylase/oxygenase (RubisCO), a key enzyme in the Calvin-Benson cycle (Whittenbury and Dalton, 1981;Whittenbury, 1981). Several Methylococcus-related methanotrophs have been described including the genera Methylocaldum (Bodrossy et al, 1997;Takeuchi et al, 2014), Methyloparacoccus (Hoefman et al, 2014) and Methylogaea (Geymonat et al, 2010). Members of these genera form a monophyletic cluster in pmoA gene-based trees and are lately addressed as type Ib methanotrophs.…”
Section: Introductionmentioning
confidence: 99%
“…In the last 10 years, novel cultivation techniques have enabled the isolation of previously uncultured methane oxidizers; the characterization of these new genera has led to an improved understanding of methanotroph taxonomy (Bowman et al, 1993(Bowman et al, , 1997Bodrossy et al, 1997;Dedysh et al, 1998Dedysh et al, , 2000Dedysh et al, , 2002Wise et al, 1999Wise et al, , 2001. Methanotrophs are currently classified as type I methanotrophs (comprising nine genera among the g-proteobacteria) and type II methanotrophs (comprising four genera among the a-proteobacteria), according to their intracytoplasmic membrane structure, carbon assimilation pathways, fatty acid composition and phylogeny (Hanson and Hanson, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The type I methanotrophs have been taxonomically united to form the family Methylococcaceae, of which four genera were originally distinguished on the basis of phospholipid fatty acid patterns, 16S rDNA analysis and phenotypic traits : Methylococcus, Methylomonas, Methylobacter, Methylomicrobium (Bowman et al, 1993, 1995. More recently, the ecological and phylogenetic diversity of the Methylococcaceae has expanded considerably as members of a psychrophilic genus, Methylosphaera (Bowman et al, 1997), and thermophilic genera, Methylocaldum and ' Methylothermus ' (Bodrossy et al, 1997(Bodrossy et al, , 1999, have been described.Previously, we reported on the use of an extinctiondilution enrichment method to isolate novel methanotrophs from landfill cover soil in the southeastern USA (Wise et al, 1999). 16S rDNA analysis of two type I isolates, designated AML-C10 T and AML-D4 T , showed that they were members of a novel methanotrophic phylotype as defined by clone sequences retrieved from directly extracted soil DNA.…”
mentioning
confidence: 99%